2022
DOI: 10.3389/fenvs.2022.1018801
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the changes of the monetary value of mangrove ecosystem services in China and its application

Abstract: With the development of marine economy and climate changing, the ecological value of mangrove ecosystem has become increasingly prominent. In this study, the ecological values of China’s mangrove ecosystem services was evaluated based on the four services and nine functions of mangrove ecosystem. On this basis, the dynamic changing characteristics of the nine mangrove ecological values from 2001 to 2019 were analyzed. The results indicated that the top four service values were that of preventing coastal erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Field measurements were conducted in two study sites on Hainan Island in the south of China, which was considered a hotspot for mangrove research and conservation due to the highest mangrove diversity and the highest carbon stock of all mangrove forests in China (Li and Lee, 1997;Lin, 1999). Haikou (HK) and Sanya (SY), located in the Northern and Southern of Hainan Island, were selected as two main sites for this study.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Field measurements were conducted in two study sites on Hainan Island in the south of China, which was considered a hotspot for mangrove research and conservation due to the highest mangrove diversity and the highest carbon stock of all mangrove forests in China (Li and Lee, 1997;Lin, 1999). Haikou (HK) and Sanya (SY), located in the Northern and Southern of Hainan Island, were selected as two main sites for this study.…”
Section: Study Sitesmentioning
confidence: 99%
“…However, one-third of the total world mangrove area has been lost during the last half-century due to human activity or climate change (Kuenzer et al, 2011;Hamilton and Casey, 2016). The mangrove in Hainan Island is considered a hotspot for mangrove research and conservation due to the highest mangrove diversity and the highest carbon stock of all mangrove forests in China (Li and Lee, 1997;Lin, 1999). From 1950 to 2010, the mangrove area of Hainan sharply reduced by 60% (Liao and Zhang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves are woody plant communities distributed in tropical and subtropical intertidal zones that play a vital role in reducing the impact of natural disasters and maintaining the coastal ecological environment (Lin, 1999). Kandelia, a typical viviparous mangrove species in the Rhizophoraceae family, is widely distributed from Ganges Delta, Burma, through the South China Sea to southern China, and southern Japan (Tomlinson, 1986;Sheue et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Kandelia, a typical viviparous mangrove species in the Rhizophoraceae family, is widely distributed from Ganges Delta, Burma, through the South China Sea to southern China, and southern Japan (Tomlinson, 1986;Sheue et al, 2003). Kandelia obovata (known as K. candel until 2003) is one of the most important and dominant mangrove species naturally distributed along the coastal areas of southeastern China with the widest distribution and the highest latitude, including in Hainan, Guangdong, Guangxi, and Fujian, in addition to Hong Kong, Macao, and Taiwan (Li & Lee, 1997;Lin, 1999). As the strongest cold-resistant true mangrove species, it is not only a high-quality mangrove species that has been artificially planted for ecological restoration of northward coastal wetlands in China (Liao & Zhang, 2014), such as Yueqing in Zhejiang Province, but also an ideal plant material suitable for exploring the relationship between genetic variation and geographical distribution of mangrove species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that, along with external transformations, mangroves in China have been undergoing a process of degradation over the past 2 -3 decades, leading to the disappearance of two-thirds of the original mangrove forests [8] [9] [10]. Coastal reclamations for harbors, seawalls and aquacultural ponds have become the major factor for the loss of intertidal wetlands, altered the hydrology and the interaction between terrestrial ecosystems and marine ecosystems, leading to profound detriments to ecological succession and resilience [11] [12] [13].…”
Section: Introductionmentioning
confidence: 99%